An investigation of magnetic nanofluids for various thermal applications - Fu, Rong (2017)
Magnetic nanofluid (MNF) is one special kind of nanofluid which possesses both magnetic and fluid properties. Nowadays, extensive attention has been focussed on development of thermal applications. Investigations of magnetic hyperthermia are emerging as a new frontier in studies of cancer therapy. The theory of treatment is based on the fact that magnetic nanoparticles produce heat under an AC magnetic field via a mechanism called magnetic losses. Facing with the present technical limits and growing demands for safe treatment, researchers have realized the advantage of assembling superparamagnetic nanoparticles (SMNP) into colloidal clusters for effective heating at low field intensity and frequency. In contrary to the isolated particles, the magnetic losses of the clusters are affected by inter-particle dipole interactions. The role of dipole interactions is complex and contradictory findings have been reported. Understanding the role of dipole interactions is the key to optimizing the clusters for efficient hyperthermia heating.